Preoperative direct oral anticoagulants treatment and all-cause mortality in elderly patients with hip fracture: A retrospective cohort study. Issue 189 (May 2020) - Saliba, Walid; Arbel, Anat; Abu-Full, Zomoroda; Cohen, Shai; Rennert, Gad; Preis, Meir
Abstract: Introduction: Hip fracture is common among the elderly and is associated with increased morbidity and mortality, particularly when surgery is delayed. Direct oral anticoagulants (DOACs) use might increase bleeding and postpone hip repair surgery. We aimed to assess the association between preoperative DOACs use and adverse outcomes in elderly patients with hip fracture. Materials and methods: This retrospective cohort study included all elderly patients (≥65 years), from the district of Haifa and Western Galilee, Israel, who underwent hip repair surgery for hip fracture between 2014 and 2018. Regression models with adjustment for propensity score were used to assess the association with all-cause mortality and other adverse outcomes. Results: A total of 3418 patients with hip fracture were included of whom 163 (4.8%) were vitamin K antagonists (VKAs) users and 247 (7.2%) were DOCAs users. Propensity score adjusted models revealed that, compared to no anticoagulants use, DOACs use were independently associated with decreased risk of 30-day and 90-day mortality; HR 0.38 (95% CI, 0.17–0.88) and 0.47 (0.27–0.82), respectively. No significant associations were detected between VKAs use and all-cause mortality, compared to no anticoagulants use. DOACs and VKAs had significantly longer waiting time for hip repair surgery, and longer stay in hospital. DOACs and VKAs users had a non-significant higher estimated intraoperative bleeding. However, only VKAs users required a significantly higher number of blood transfusions. Conclusions: Albeit being associated with longer waiting time for surgery and longer hospitalization, DOACs use appears to be associated with reduced risk of mortality among elderly patients with hip fracture. Highlights: DOACs use is associated with decreased mortality in patients with hip fracture. DOACs use is not associated with blood transfusion in patients with hip fracture. DOCAs use is associated with surgery delay in patients with hip fracture. DOCAs use is associated with longer hospital stay in patients with hip fracture.